Individualization : institutionalized individualism and its social and political consequences - Beck, Ulrich, 1944-2015 (Theory, culture & society (Unnumbered), 2002)
The authors perceive that we humans are in the midst of a fundamental change in the nature of society and politics. This change hinges on the two processes of globalisation and individualisation.